Changes in novel gastrointestinal and renal injury markers in the blood plasma of sheep following increasing intravenous doses of tolfenamic acid - Yildiz, Ramazan; Corum, Orhan; Atik, Orkun; Durna Corum, Duygu; Altan, Feray; Ok, Mahmut; Uney, Kamil (Akademiai Kiado Zrt., 2019)
The administration of high doses of non-steroidal anti-inflammatory drugs (NSAID), such as tolfenamic acid (TA), has undesirable effects on different organs. Some novel biomarkers have been reported that can determine the gastrointestinal and renal injury caused by a high dose of NSAIDs or other toxic substances. This study was aimed at determining the changes in gastrointestinal (TFF2 and HYP), renal (NGAL and KIM-1) and cardiac (cTn-I, CK-MB) injury markers after the use of increasing intravenous doses of TA in sheep. TA was administered intravenously to groups of six sheep each, at the dose levels of 0 (Group 0, i.e., G0), 2 (G2), 4 (G4), 8 (G8) and 16 (G16) mg/kg. The concentrations of the studied biomarkers were measured at 3, 9, 18 and 36 h after administration of TA. The TFF2 and NGAL concentrations in G16 were found to be significantly higher (P < 0.05) than in the other groups except for G8 at different sampling times. HYP concentration in G16 was observed to be significantly (P < 0.05) lower than that in all other groups at 36 h. KIM-1 level in G16 was significantly (P < 0.05) higher than in all other groups at different sampling times. An increase in the renal markers, KIM-1 and NGAL, in G8 was observed before any change in plasma creatinine and urea. The cardiac marker cTn-I in G16 was significantly (P < 0.05) higher than in other groups at different sampling times. The results showed that the novel biomarkers (HYP, TFF2, NGAL, and KIM-1) can be used to determine gastric and renal injury in sheep.
Keywords: Gastrointestinal; Sheep; Dose-Response Relationship, Drug; Gastrointestinal Diseases; Anti-Inflammatory Agents, Non-Steroidal; Sheep Diseases; Injury; SV Veterinary science / állatorvostudomány; Tolfenamic Acid; Animals; Administration, Intravenous; Female; Kidney Diseases; ortho-Aminobenzoates; Renal; Cardiac; Biomarkers; 2. Zero hunger